Teacher's Strategy in Developing Pedagogical Competence to Improve the Effectiveness of Fiqh Learning - Nurhajidah, Nurhajidah; Hidayatullah, Syarif (Darajatuna: Interdisciplinary Journal of Islamic Studies, 2025)
This study aims to analyze the teacher's strategy in developing pedagogical competence to improve the effectiveness of Fiqh learning. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results showed that teachers' pedagogical competence plays an important role in creating interactive and applicable learning. The strategies applied include the use of innovative learning methods, the utilization of technology, and contextual approaches that are relevant to students' daily lives. Supporting factors for the success of this strategy include students' enthusiasm for learning, the availability of learning media, and the support of the school environment. However, there are obstacles such as limited facilities and lack of variety in teaching methods that are still a challenge. The conclusion of this study confirms that strengthening teachers' pedagogical competence through continuous training and support from educational institutions is a strategic step in improving the effectiveness of Fiqh learning. Therefore, the main recommendation of this study is the need to develop a program to improve teacher competence in order to be able to design more interesting and meaningful learning for students